Cryoablation of Primary Breast Cancer in Patients with Metastatic Disease: Considerations Arising from a Single-Centre Data Analysis. (19th October 2017) - Pusceddu, Claudio; Melis, Luca; Ballicu, Nicola; Meloni, Paolo; Sanna, Valeria; Porcu, Alberto; Fancellu, Alessandro
Abstract : Background. Patients presenting with stage IV breast cancer might benefit by removal of the primary tumor. We report our experience with CT-guided cryoablation of the primary tumor, with the aim of evaluating its role in this subgroup of patients. Patients and Methods. Data of 35 patients with mean age of 58 years with breast cancer at stage IV submitted to CT-guided cryoablation of the primary tumor between 2010 and 2016 were prospectively evaluated. All patients, except three, were preoperatively and postoperatively evaluated with breast MRI to assess the extent of tumor necrosis. Retreatment was performed in case of incomplete ablation. Results. Mean tumor size was 3.02 ± 1.4 cm. Six patients had multicentric disease. Complete tumor necrosis was 85.7% and 100% at 2-month and 6-month follow-up, respectively, as 5 patients with tumors > 3 cm required a redo cryoablation. No patient developed major complications. Minor side effects occurred in 30 patients (82%). All patients were discharged the same day of the procedure. During a mean follow-up of 46 months (range 3–84), 7 patients (20%) experienced local recurrences that were treated with redo cryoablation, and 7 (20%) died for disease progression. Conclusions. Our results suggest that cryoablation of the primary tumor is safe and effective in the treatment of patients presenting with stage IV breast cancer.